Kwestie doboru małżeńskiego w międzykulturowych małżeństwach mieszanych - Jodłowska-Herudzińska, Małgorzata (Wydawnictwo Naukowe UAM, 2002)
In general, it is considered that the level o f similarities between the spouses, especially the cultural similarities determines a success in the marriage and the marital satisfaction. The heterogamy concerning mostly the characteristics, such as the differences in nationalities, the religious believes and race, it might weight down the marital life and the family life. It is not uncommon that the heterogamy is disapproved by the public view, in contras to endogamy Usually the spouses are the same nationality, live in the same city, have similar level o f education, often belong to the same working group and have similar social background The relationships, which are the object of this article, are only the small part o f all marriages. But the question is: are they destined to fail from the very begging? Following the main idea of Rosset E.(1986): the belief in the beneficial power of endogamy is only a product o f conservative thinking, which, in fact, is a relic of the past. The endogamy, as such, doesn’t solve marital differences in opinions, but on the other hand, the exogamy opens for the spouses the possibility of integration various aspects: the customs, the different traditions, which can make their life more interesting and emotionally fulfilling. Nevertheless, the heterogamy is one of the main factors, which portend difficulties before the actual marriage has even started, might cause a great stress while being married and might lead not only to its disorganization, but also to its disintegration. What kind of people, or more, what the social -demographical characteristics built the multicultural mixed marriages and what an influence of the combination of all the factors in given marriages has on the quality and the maritiai durability, all these are the main, beside more detailed questions on which, an author hopes that the reader will find the answers to in this article.
Issues of the marriage selection in the multicultural mixed marriages